Talanoa: A contemporary qualitative methodology for sport management. Issue 1 (February 2017) - Stewart-Withers, Rochelle; Sewabu, Koli; Richardson, Sam
Highlights: Indigenous approaches to research allow sport management researchers to examine their roles in knowledge production. Sport management researchers should be contributing to the broader conversations regarding decolonizing indigenous research. Where possible, sport management researchers should work collaboratively and create opportunities for capacity building of local researchers. Appropriately deigned research which informs our understanding about cultural diversity is fundamental if inclusiveness is to occur. For a more nuanced understanding of all dimensions of sport management, research from a multitude of paradigms will need to occur. Abstract: In an interconnected world, and with cultural diversity ever present, there is growing recognition in sport management for the need to understand such diversity alongside the desire for more inclusive organisations and processes. Research which informs these understandings is thus fundamental. Planning and doing research in an environment where the culture is different can, however, add a level of complexity to the research. No matter the project phase - conception, design, data collection or analysis - cultural consideration must be given (Johnston, 2014 ). Those undertaking research in differing cultural settings often look to find a research approach which marries with the cultural context. In the Pacific region, or for those working with Pacific people, a popular choice is talanoa. Drawing on empirical work with Pacific rugby athletes, the authors outline the talanoa process – an "embodied expression of the vanua concept" (Farrelly & Nabobo Baba, 2012, p. 1 ). Ethical issues, challenges, and opportunities in using this approach are reflected on, and the value of talanoa to sport management research and in particular the sub-field of sport-for-development is considered. The authors argue the importance of talanoa as a culturally-appropriate contemporary qualitative research approach when working with Pasifika people or Pasifika issues. Approaches such as talanoa are valuable for challenging sport management researchers to further examine their own roles in the process of producing sport-specific knowledge; for decentring current approaches to sport management research and for shifting the discipline towards politicization; as well as contributing to broader conversations regarding decolonising indigenous research (Shaw & Hoeber, 2016; Skinner & Edwards, 2010; Skinner et al., 2014).